ANALYSIS OF YOUTUBE USER RESPONSES TO THE DISCUSSION OF NASDEM POLITICIAN IRMA SURYANI: A CORPUS-BASED DISCOURSE ANALYSIS - Robing, Robing; Rexsy, Muhammad; Putri, Friska Nabila; Reffo, Reffo; Yulianti, Yulianti (Journal of Social Politics and Governance (JSPG), 2025)
This case study examines YouTube user responses to a video titled “Discussing Fraudulent Elections, Irma from NasDem Bluntly Criticises Political Parties, Jokowi, and Samsul.” The main objective of this study is to identify the speech acts expressed by users, focusing on their responses directed toward the media, Irma herself, and her statements regarding election fraud and the right of inquiry alongside PDI-P politicians. The primary data consists of YouTube comments compiled into the Irma Response Corpus corpus. The analysis reveals a rich variety of user responses—some supportive, some rejected, and others skeptical, each adding a layer of complexity to the discourse. These findings affirm that YouTube is a video-sharing platform and a discursive arena for active, emotional, and participatory political engagement. Corpus-assisted Discourse Studies (CADS) proved effective in uncovering lexical patterns and discourse dynamics that emerge organically in digital communication. This study opens up opportunities for further research in digital political communication, particularly those that explore citizen interactions within an increasingly fragmented media ecosystem.